2017
DOI: 10.1016/j.ebiom.2017.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Loss of MyoD Promotes Fate Transdifferentiation of Myoblasts Into Brown Adipocytes

Abstract: Brown adipose tissue (BAT) represents a promising agent to ameliorate obesity and other metabolic disorders. However, the abundance of BAT decreases with age and BAT paucity is a common feature of obese subjects. As brown adipocytes and myoblasts share a common Myf5 lineage origin, elucidating the molecular mechanisms underlying the fate choices of brown adipocytes versus myoblasts may lead to novel approaches to expand BAT mass. Here we identify MyoD as a key negative regulator of brown adipocyte development.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 52 publications
4
64
0
Order By: Relevance
“…As a consequence, CK2b deletion prevents also the appearance of the later muscle differentiation markers and the formation of myotubes ( Fig. 2A-C, E), similarly to the phenotype previously described in Myod1 2/2 cells (61,62,64). Notably, the CK2b effect on MyoD expression seems to be independent of the CK2 catalytic subunits and holoenzyme activity based on the following pieces of evidence: 1) changes in MyoD protein level parallel those of CK2b (Fig.…”
Section: Discussionsupporting
confidence: 79%
“…As a consequence, CK2b deletion prevents also the appearance of the later muscle differentiation markers and the formation of myotubes ( Fig. 2A-C, E), similarly to the phenotype previously described in Myod1 2/2 cells (61,62,64). Notably, the CK2b effect on MyoD expression seems to be independent of the CK2 catalytic subunits and holoenzyme activity based on the following pieces of evidence: 1) changes in MyoD protein level parallel those of CK2b (Fig.…”
Section: Discussionsupporting
confidence: 79%
“…Several recent reports demonstrated that Prdm16 could also be suppressed post-transcriptionally in both myoblasts and white preadipocytes by miR-133, a cardiac and skeletal muscle-enriched microRNA (i.e., MyomiR) (Liu et al, 2013b;Pasut et al, 2016;Trajkovski et al, 2012;Yin et al, 2013b). Interestingly, miR-133 was also shown to be a direct transcriptional target of MyoD in cultured myoblasts (Pasut et al, 2016;Rao et al, 2006;Wang et al, 2017). In freshly isolated MPCs, we confirmed that miR-133 was indeed transcriptionally regulated by both MyoD and Myf5 ( Figure S6A).…”
Section: Dual Roles Of Myod/myf5 In Mpcssupporting
confidence: 79%
“…The critical role of MyoD/Myf5 in suppressing the BA fate is also supported by existing data in literature. In a most recent study, deletion of Myod in myoblasts was also found to promote the cell fate change to BA in culture (Wang et al, 2017). In addition, in Myod/Myf5 double-KO mouse embryos, excessive fat tissues were found in the muscle-forming regions at the expense of muscles (Kablar et al, 2003).…”
Section: Dual Roles Of Myod/myf5 In Mpcsmentioning
confidence: 90%
See 1 more Smart Citation
“…The identification of MyoD and the MyoD family of myogenic regulatory factors (MRFs) has revealed that the myogenic potential is determined by the expression of transcription factors that influence myogenic gene expression. Conversely, the loss of MyoD and/or MRFs in skeletal myoblasts, both in vitro in C2C12 cells [ 11 , 12 ] and in vivo , suppresses skeletal myogenesis [ 13 , 14 ]. During differentiation, together with Pbx homeodomain protein, MyoD binds to the regulatory regions of myogenic genes, including Myog , Mylpf , Myh3 , Tnni and Ryr1 [ 15 ], which triggers chromatin remodelling by recruiting the SWI/SNF chromatin remodelling factor Brg1 for myogenic gene transcription [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%